1999
DOI: 10.1038/sj.bjc.6690131
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency of benzoporphyrin derivative in the photodynamic therapy of pigmented malignant melanoma

Abstract: Summary Benzoporphyrin derivative monoacid ring A (verteporfin, BPD-MA) when intravenously injected (5.5 µmol kg -1 ) to C57/BL6 mice bearing a subcutaneously transplanted B1 melanoma gave a maximal accumulation in the tumour within 1-3 h with recoveries of 1.84-1.96 µmol kg -1 . Irradiation of BPD-MA-loaded melanoma with 690-nm light from a dye laser at 3 h and 9 h post injection induced tumour necrosis and delay of tumour growth of 28 and 14 days respectively. The response of the tumour to BPD-MA photosensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…A second-generation drug, benzoporphyrin derivative monoacid ring A (BPDMA, Verteporfin), has received Food and Drug Administration (FDA) approval in the United States for the treatment of age-related macular degeneration, [21] and is recognized as a potent photosensitizer for non-melanoma [22] and melanoma skin cancer. [23,24] Aminolevulinic acid (ALA)-based photosensitizers have been approved for the treatment of actinic keratoses and are in clinical use, most notably under the commercial names Levulan and Metvix. However, patients repeatedly report experiencing pain in ALA-PDT.…”
Section: Introductionmentioning
confidence: 99%
“…A second-generation drug, benzoporphyrin derivative monoacid ring A (BPDMA, Verteporfin), has received Food and Drug Administration (FDA) approval in the United States for the treatment of age-related macular degeneration, [21] and is recognized as a potent photosensitizer for non-melanoma [22] and melanoma skin cancer. [23,24] Aminolevulinic acid (ALA)-based photosensitizers have been approved for the treatment of actinic keratoses and are in clinical use, most notably under the commercial names Levulan and Metvix. However, patients repeatedly report experiencing pain in ALA-PDT.…”
Section: Introductionmentioning
confidence: 99%
“…The employment of selected second-generation photosensitizing agents, such as Si(IV)-naphthalocyanine, bacteriochlorin a and Lu(III)-texaphyrin, characterized by an extended macrocycle and high molar absorptivity in the 750-800 nm spectral interval improved the efficacy of PDT on experimentally implanted melanotic melanoma (Schuitmaker, van Best et al 1990;Biolo, Jori et al 1996;Woodburn, Fan et al 1998). Ten years later since the first study, Busetti et al showed that if the melanosomes were preirradiated with high peak power pulsed laser radiation at 1064 nm, PDT treatment was improved (Busetti, Soncin et al 1999). In 1999 the same group investigated the effect of PDT using a benzoporphyrin derivative monoacid ring A (verteporfin, BPD-MA), against B16 pigmented melanoma, after preirradiation.…”
Section: Pdt and Melanomamentioning
confidence: 99%
“…Especially in heavily pigmented melanomas, it is already known that PDT with Photofrin is ineffective owing to the strong absorbance of melanin in the 630-nm range, which is the wavelength that is used to activate Photofrin in clinical PDT. However, studies demonstrated that by using second-generation photosensitizing agents characterized by high molar absorbance in the 750-800 nm spectral interval such as Si (IV)-naphthalocyanine, bacteriochlorin a and Lu (III)-texapyrin, where melanin exhibits a small residual absorbance, thereby minimizing the optical filtering action, melanotic melanoma can be made responsive to PDT (Busetti, Soncin et al 1999). …”
Section: Melanoma Resistance To Pdtmentioning
confidence: 99%
See 2 more Smart Citations